O povoamento romano do Concelho de Oeiras: antecedentes, economia e sociedade (séculos I a.C. a V d.C.) - Cardoso, João Luís; André, Maria da Conceição (Estudos Arqueológicos de Oeiras, 2020)
A synthesis of the Roman occupation of the municipality of Oeiras is presented. The data obtained reveals an early Italic influence, since the beginning of the Empire, in continuity with the strong Mediterranean presence verified in the end of the Iron Age. The occupation of the territory, had an essentially agrarian character, related to the polyculture carried out in the various villae rusticae identified, especially implanted in calcareous soils, partly related to the supply of the great city that was the city of Olisipo at the time, ca. 15 km away, but easily connected by the Tagus river. The archaeological remains comprise many imported products, revealing the openness to Mediterranean trade, a reality that remained even after the fall of the Empire, being proved by the 6th century AD phocean ceramic productions. In addition, the existence of two funerary epigraphs reinforce the ide integration of these communities in the Roman Empire since the 1st century AD. One of them reveals by the typology, the adoption of Roman models by the population, already widely acculturated, as it is denounced by the cognomen of the deceased, clearly indigenous. The other epigraph reveals at the same time, a harmonic acculturation accompanied by an evident cosmopolitism, since it corresponds to the grave of a aquilifer of second legion, who, being a native here, will have traversed several areas of the Empire, before returning to their homeland, where he probably ended his military career.